Cross‐polarization optical coherence tomographic assessment of in situ simulated erosive tooth wear. Issue 9 (17th June 2021) - Romero, Maria Jacinta Rosario H.; Bezerra, Savio J. C.; Fried, Daniel; Yang, Vincent; Lippert, Frank; Eckert, George J.; Zero, Domenick T.; Hara, Anderson Takeo
Abstract: This clinical study tested cross‐polarization optical coherence tomography (CP‐OCT) monitoring of erosive tooth wear (ETW). Twenty participants completed a 14‐day/arm, 3‐arm crossover study simulating different ETW severities. Participants received two enamel specimens (per arm) and were randomized to: severe (s‐ETW, lemon juice/pH:2.5/4.25%wt/vol citric acid), moderate (m‐ETW, grapefruit juice/pH:3.5/1.03%wt/vol citric acid), and non‐ETW (water). Enamel thickness was measured with CP‐OCT (day[D] 0, 7, 14) and micro‐computed tomography (μ‐CT; D14). Enamel surface loss was determined with CP‐OCT and optical profilometry (OP; D7, D14). CP‐OCT showed higher enamel surface loss for D14 than D7 for m‐ETW ( P  = .009) and s‐ETW ( P  = .040) and differentiated severity at D14 (s‐ETW > non‐ETW, P  = .027). OP was able to differentiate surface loss between days (D7 < D14, P  < .001) for m‐ETW and s‐ETW, and ETW severity effect after 7 and 14 days (non‐ETW < m‐ETW < s‐ETW, P  < .001). At D14, CP‐OCT and μ‐CT were positively correlated ( r  = .87, ICC = .62). CP‐OCT showed potential as a tool for clinical ETW monitoring. Abstract : Cross‐polarization Optical Coherence Tomography (CP‐OCT) is a non‐invasive and non‐destructive imaging tool that can be used to assess erosive tooth wear (ETW) in vitro. This study aimed to evaluate CP‐OCT monitoring of more clinically relevant ETW lesions through a longitudinal crossover in situ ETW model of different severities and validate with micro‐computed tomography and optical profilometry. The results confirm the potential of CP‐OCT use for clinical ETW assessment and monitoring.